The Influence of Motivation, Leadership Style and Work Environment on Employee Performance Through Discipline in the Merangin Regency Fire and Rescue Service Command Headquarters Officer Unit - Zahari, M.; Akbar, Ali; Daryanto, Daryanto (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The objective of this research is to obtain an overview and describe the motivation, leadership style, work environment, discipline, and performance of employees; as well as to identify and analyze the direct and indirect effects of motivation, leadership style, and work environment on the discipline and performance of employees at the Fire and Rescue Department. The population in this study consists of 76 staff members of the Command Headquarters of the Fire and Rescue Department in Merangin Regency, based on conditions in 2024. Partial Least Square (PLS) data analysis and a survey method are used in this quantitative study. The validity and reliability of the outer model were examined prior to the study. Then, R-Square (coefficient of determination) and F-Square (f2 effect size) were used to test the inner model. The study's findings indicate that, both directly and indirectly through work discipline, leadership style and work environment have a favorable and significant impact on employees' performance at the Fire and Rescue Department's Command Headquarters in Merangin Regency. It has been discovered that motivation has little bearing on worker performance, either directly or indirectly, through work discipline.